Partial substitution of chemical fertilizer with organic fertilizer: a promising circular economy approach for improvement soil physical and chemical properties and sustainable crop yields - Chen, Qian; Xie, Junhong; Li, Lingling; Khan, Khuram Shehzad; Wang, Linlin; Chang, Lei; Du, Changliang (Frontiers in Plant Science, 2025)
IntroductionFood security faces multiple challenges, and increasing crop yields is an effective way to address this issue. Replacing chemical fertilizers (CFs) with organic fertilizers can affect soil nutrient cycling and hence crop yields, with changes in organic carbon content being an important way in which soil nutrient content affects crop production. However, the dynamics of the effect of organic fertilizer substitution on soil organic carbon and the mechanism by which it further contributes to yield formation are not clear.MethodsTo this end, a 2 - year maize field experiment (2019-2020) was conducted to study the effect of organic substitution on soil properties, organic carbon fractions, and maize yields. Six treatments were applied: no fertilizer (CK), CF, and four different organic substitution rates (50%, 37.5%, 25%, and 12.5%), denoted by (50% OF), (37.5% OF), (25% OF), and (12.5% OF), respectively. Fully film - mulched double ridge-furrow technology was used to optimize water retention and soil temperature.ResultsResults demonstrated that 12.5% OF reduced water consumption by 1.40% during critical maize growth stages compared to CF. It also increased 0-30 cm total phosphorus (TP) by 15.09%, soil porosity by 4.82%, and available phosphorous (AP) by 34.81% at harvest, respectively, compared with CK of 2 years average. Partial substitution of CF with organic fertilizer led to a significant increase in soil organic carbon (SOC) and fractions through improvement in physicochemical properties. The 12.5% OF at 0-30 cm soil layer significantly increased easily oxidizable organic carbon (EOC) by 33.23%, SOC by 2.18%, and particulate organic carbon (POC) by 6.64% compared to CF, respectively. At 10-30 cm, 37.5% OF increased microbial biomass carbon (MBC) by 9.90% and hot water-soluble carbon (HOC) by 6.90% compared to CF. Under 12.5% OF, an EOC increased by 13.20% at 0-5 cm, while dissolved organic carbon (DOC) and light fraction organic carbon (LFOC) rose by 18.65% and 37.13% at 0-10 cm, respectively. Interestingly, the 12.5% OF boosted grain yields by 6.60% and biomass by 4.59% compared to CF, and by 213.02% and 208.13% compared to CK. Water use efficiency (WUE) increased by 11.43% and 153.27% under CK and CF treatment, respectively. Randomized forest analysis highlighted that increases in soil MBC, HOC, and DOC content were critical for maize yield improvement.DiscussionIn summary, 12.5% OF and 37.5% OF can increased MBC, HOC, and DOC content by increasing soil porosity, TP and AP content and decreasing soil water depletion, thereby increasing crop yield. Compared to 37.5% OF, 12.5% OF was more environmentally sustainable, increased crop yields, and increase economic benefits. This provided a theoretical basis for partial substitution of CF with organic fertilizer to improve soil health and crop yield. The present study showed that 12.5% OF (200 kg hm-2 of N) was a suitable cropping pattern in the region and was recommended for wider use in the region.